Role and function of the 26S proteasome in proliferation and apoptosis - Naujokat, Cord; Hoffmann, Stephan (Laboratory investigation, 2002)
The 26S proteasome constitutes the central proteolytic machinery of the highly conserved ubiquitin/proteasome system, the cell's major tool for extralysosomal protein degradation. Recently, a plethora of cell proteins implicated in the regulation of basic cellular processes, such as proliferation, differentiation, cell cycling, and apoptosis have been discovered to undergo processing and functional limitation by entering the ubiquitin/proteasome pathway with the final destination to be proteolytically degraded by the 26S proteasome. Because both negative and positive regulators of proliferation and apoptosis undergo proteasomal degradation in a tightly regulated and temporally controlled fashion, the 26S proteasome can play opposite roles in the regulation of proliferation and apoptosis. These roles are apparently defined by the cell's environment and proliferative state. Finally, proteasomal protein degradation is deregulated in a number of human diseases, including cancer and neurodegenerative and myodegenerative diseases, which all exhibit an imbalance of proliferation and apoptosis. An improved understanding of the modes of proteasomal action should lead to the development of beneficial therapeutic and diagnostic strategies in the future.
Gesehen am 19.02.2021